Tailoring Coulomb correlations in twisted WSe2bilayers - Merkl, Philipp; Mooshammer, Fabian; Brem, Samuel; Girnghuber, Anna; Lin, Kai Qiang; Weigl, Leonard; Yong, Chaw Keong; Gillen, Roland; Maultzsch, Janina; Lupton, John M.; Malic, Ermin; Huber, Rupert (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
Phase-locked few-cycle mid-infrared pulses trace how the twist angle alone renormalizes the binding energy of excitons in twisted WSe2 homobilayers by a factor of two and tunes their lifetime by a factor of twenty.
CRIS-Team Scopus Importer:2021-12-24